Marble Powder as a Sustainable Cement Replacement: A Review of Mechanical Properties - Abbas, Moutaman M.; Muntean, Radu (MDPI AG, 2025)
The sudden increase in industrialization has reduced the availability of natural building materials and triggered the growing awareness of sustainable practices within the construction industry. The study presented here deals with marble powder, which is one of the by-products obtained from the marble industry, as a cement replacement in concrete mixtures. The main aims will be to investigate the impact of marble powder waste materials on the mechanical properties of concrete and to promote the recycling of various industrial wastes for environmental sustainability. Material testing was conducted with the levels of substitution of marble powder for cement ranging from 0% to 50%, and the resulting concrete was evaluated for compressive and tensile strength over different curing periods. The results show that concrete compressive strength and tensile strength are most efficiently improved when marble powder replacement is up to 10–15%, attaining its full potential after 28 days. Beyond this replacement level of 15%, the mechanical properties decrease, suggesting that higher substitution levels may not be effective. This paper consolidates findings, provides a novel comparative analysis, and addresses key challenges regarding the use of marble powder, providing room for the future industrial development of supplementary cementitious materials (SCMs), eventually leading to sustainability in the construction sector.